A Predictive Batch Culture Growth and Biosynthesis for Bacillus cereus (ATCC 14579) using Response Surface Methodology (Journal of Environmental Bioremediation and Toxicology, 2022)
Optimization studies of Bacillus cereus (ATCC 14579) tolerance to stress phenomenon could serve as a basic prerequisite for its utilization in future biotechnological research. Successful cell culture at optimum parametric conditions was found to prepare the cells to withstand upper and lower range values depending on the need and purpose. This study was performed to develop a predictive optimum model for the growth of this mesophilic bacterium, B. cereus in batch culture shake flasks. The linear and mutual interactions effects of nutrient availability (4-16 g/L) and composition, temperature (30-40 oC) and agitation (140 - 200 rpm) collectively termed as growth regulators were sought using central composite face-centred design (CCFD) response surface methodology (RSM). The effectiveness of the independent variables on the dependent variable was weighted and validated using statistical and graphical indices which spelt a suitable predictive model for B. cereus growth and biosynthesis. This model provided an efficient and reliable approach for predicting the growth of B. cereus as a function of the growth-influencing markers. The results showed that the model term is highly significant at P >0.0001 and a well-correlated adjusted R2 and predicted R2 of less than 1.0 (0.9984). Moreover, the coefficient of determination value of only 1.45 % variability as well as agreed predictive (3.01) versus experimental (3.0) values depicted that the hidden (noise) effect was very minimal. Therefore, the model further confirmed the versatility of the isolate to simple growth nutrient within defined optimal physical operational parameters of simple shake flask culture.
Keywords: Optimization; Growth; Bacillus cereus; Batch mode; Central composite face-centred design (CCFD; RSM